2005
DOI: 10.1021/bi050882k
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Affinity of SecA for Signal Peptide in Different Environments

Abstract: SecA, the peripheral subunit of the Escherichia coli preprotein translocase, interacts with a number of ligands during export, including signal peptides, membrane phospholipids, and nucleotides. Using fluorescence resonance energy transfer (FRET), we studied the interactions of wild-type (WT) and mutant SecAs with IAEDANS-labeled signal peptide, and how these interactions are modified in the presence of other transport ligands. We find that residues on the third α-helix in the preprotein cross-linking domain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 66 publications
3
48
1
1
Order By: Relevance
“…Wild-type SecA protein bound PhoA signal peptide with an affinity of 2.4 Ϯ 0.8 M, in agreement with previously published values ( Table 2; see also Fig. S1 in the supplemental material) (2,3,31). Most of our SecA mutant collection had signal peptidebinding affinity constants that were within 3-fold of wild-type SecA, indicating that the relevant substitution had a modest effect or no effect on SecA signal peptide binding.…”
Section: Isolation Of Seca Signal Peptide-binding-defective Mutantssupporting
confidence: 91%
See 1 more Smart Citation
“…Wild-type SecA protein bound PhoA signal peptide with an affinity of 2.4 Ϯ 0.8 M, in agreement with previously published values ( Table 2; see also Fig. S1 in the supplemental material) (2,3,31). Most of our SecA mutant collection had signal peptidebinding affinity constants that were within 3-fold of wild-type SecA, indicating that the relevant substitution had a modest effect or no effect on SecA signal peptide binding.…”
Section: Isolation Of Seca Signal Peptide-binding-defective Mutantssupporting
confidence: 91%
“…A number of studies have utilized genetically mutated, truncated, or proteolytically cleaved SecA proteins along with signal peptide-binding or cross-linking assays to map portions of the relevant ligandbinding site on SecA (3,31,32,37). At best, such approaches are of limited utility because either they identify a small number of residues that may or may not directly contribute to signal peptide binding or they facilitate construction of a linear rather than three-dimensional map of the actual binding site since they also include irrelevant regions and exclude relevant ones.…”
mentioning
confidence: 99%
“…Using fragments, deletional analysis, and chemical crosslinking of synthetic signal peptides, Economou's group concluded that the region at the base of the PPXD (so-called stem region) serves to bind the signal sequence. 69,89 Results of a FRET-based study with complementary crosslinking approaches also implicated the PPXD (specifically the third Using Signal Peptides to Explore Protein Export 315 helix) in signal sequence binding, 93,95 which is consistent with the early crosslinking studies from Mizushima's lab. 94 We have performed a sequence alignment of 550 SecA proteins, and the region proposed by Musial-Siwek et al 93 has a low conservation score (J. L. Maki and L. M. Gierasch, unpublished observations), raising doubt about whether it serves as a direct binding site for signal sequences.…”
Section: Seca-signal Sequence Recognitionsupporting
confidence: 61%
“…In this model PPXD and NBF-II would serve to gate the active and inactive channels of the SecYEG dimer, respectively. This suggestion is consistent with the observed extensive MPB labeling pattern of these two comparably sized domains of SecA and also with their observed functions as preprotein binding and SecA-SecYEG regulatory domains, respectively (51,52,(55)(56)(57). In this context PPXD and NBF-II labeling could occur on the same protomer or be divided between different protomers, depending on the SecA oligomeric state (monomer or dimer) as well as the SecYEG dimer orientation (front-to-front or back-to-back (29)).…”
Section: Construction Of Monocysteine Seca Mutants and In Vivosupporting
confidence: 88%
“…This result is consistent with the proposed role of PPXD as the preproteinbinding domain of SecA that transfers bound preprotein to SecYEG (51)(52)(53). Both the 219 -244 and 292-319 regions of SecA, which have been proposed to be critical for signal peptide binding (54,55), contain M/S-labeled residues. NBF-II serves a regulatory role in SecA by controlling the ATPase cycle of NBF-I, which in turn controls SecA membrane cycling (22, 56 -58).…”
Section: Construction Of Monocysteine Seca Mutants and In Vivomentioning
confidence: 99%